The toy castle. Birthday bash [videorecording (DVD)] - Jeans, Katherine A.; Jones, Rick; Olds, Elizabeth; Morris, Jorden (Questar, 2006)
Join beautiful Ballerina, handsome Soldier, graceful China Doll, playful Rag Doll, and other delightful storybook characters as they learn about friendship, self-esteem, and sharing feelings.